Utility of Cerebral Microvascular Imaging in Infants Undergoing ECMO - Luis Octavio Tierradentro-Garcia; Joseph A. Stern; Rebecca Dennis; Misun Hwang (MDPI AG, 2022)
Purpose: Infants who require extracorporeal membrane oxygenation (ECMO) therapy have an increased risk of neurological complications and mortality. Microvascular imaging (MVI) is an advanced Doppler technique that allows high-resolution visualization of microvasculature in the brain. We describe the feasibility and utility of MVI for the evaluation of cerebral microvascular perfusion in patients undergoing ECMO. Methods: We retrospectively analyzed brain MVI scans of neonates undergoing ECMO. Two pediatric radiologists qualitatively assessed MVI scans to determine the presence or absence of tortuosity, symmetry, heterogeneity, engorgement, and hypoperfusion of the basal ganglia-thalamus (BGT) region, as well as the presence or absence of white matter vascular engorgement and increased peri-gyral flow in the cortex. We tested the association between the presence of the aforementioned brain MVI features and clinical outcomes. Results: We included 30 patients, 14 of which were male (46.7%). The time of ECMO duration was 11.8 ± 6.9 days. The most prevalent microvascular finding in BGT was lenticulostriate vessel tortuosity (26/30, 86.7%), and the most common microvascular finding in the cortex was increased peri-gyral flow (10/24, 41.7%). Cortical white matter vascular engorgement was significantly associated with the presence of any poor outcome as defined by death, seizure, and/or cerebrovascular events on magnetic resonance imaging (p = 0.03). Conclusion: MVI is a feasible modality to evaluate cerebral perfusion in infants undergoing ECMO. Additionally, evidence of white matter vascular engorgement after ECMO cannulation could serve as a predictor of poor outcomes in this population.